The long dark tea-time of the soul - Adams, Douglas, 1952-2001 (Gallery Books, 2014)
When a check-in desk at London's Heathrow Airport disappears in a ball of orange flame, the event is said to be an act of God. But which god? wonders holistic detective Dirk Gently. And how is this connected to Dirk's battle with his cleaning lady over his filthy refrigerator ... or to the murder of his latest client? Or are these events just another stretch of coincidences in the life of the world's most off-kilter private investigator?